Implementasi media power spin dalam meningkatkan motivasi belajar siswa pada pelajaran fiqih X-A MA Unggulan Tlasih - Sholihah, Tsaniyatus (Maliki Interdisciplinary Journal, 2024)
Technological advancements have significantly impacted education in Indonesia, shifting teaching methods from conventional to modern, digital-based approaches. The Merdeka Curriculum, introduced by Minister of Education Nadiem Makarim for the 2024/2025 academic year, aims to address the deficiencies in learning during the COVID-19 pandemic and provide students the freedom to develop their talents, particularly in the digital realm. However, challenges such as the low interest in learning due to the attraction of social media and games persist. This study uses a descriptive qualitative approach to evaluate the effectiveness of the Power Spin learning media, which combines PowerPoint and a spin feature, in enhancing students’ motivation to learn. Based on observations and analysis in class X-A at MA Unggulan Tlasih, this media shows positive results in improving students’ focus, enthusiasm, and learning outcomes. Evaluations through questionnaires and final scores indicate that Power Spin effectively increases learning motivation, with an average final student score of 87. These findings suggest that the use of technology-based teaching media can address the challenges of modern learning and enhance the quality of education.